2009
DOI: 10.1111/j.1365-246x.2009.04132.x
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of the Alpine region from observations of seismic ambient noise

Abstract: International audienceWe use correlations of the ambient seismic noise to study the crust in western Europe. Cross correlation of 1 year of noise recorded at 150 three components broadband stations yields more than 3 000 Rayleigh wave group velocity measurements. These measurements are used to construct Rayleigh group velocity maps of the Alpine region and surrounding area in the 5–80 s period band. In the 5–10 s period band, the seismic noise recorded in Europe is dominated by surface waves originating from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
162
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 38 publications
11
162
0
3
Order By: Relevance
“…The overall structures of Fig. 13 are in good agreement with phase-velocity maps from Stehly et al (2009);Verbeke et al (2012); Molinari et al (2012).…”
Section: Phase-velocity Mapssupporting
confidence: 71%
“…The overall structures of Fig. 13 are in good agreement with phase-velocity maps from Stehly et al (2009);Verbeke et al (2012); Molinari et al (2012).…”
Section: Phase-velocity Mapssupporting
confidence: 71%
“…Under the assumption that the measurement technique of Ekström et al (1997), applied here, is accurate, this suggests that in the future we should partly replace our global Crust-2.0-based reference model with a higher-resolution, regional one, derived either from the compilation of local studies (Tesauro et al 2008), or from the inversion of ambient-noise data (Stehly et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Planned collaborative work leading to a consensus model of the European and Mediterranean upper mantle involves, most importantly, the compilation and tomographic inversion of a richer database, including surface-wave overteone (Lebedev and van der Hilst 2008), body-wave (Amaru et al 2008) and ambient-noise observations (Stehly et al 2009). In this endeavour, finite-frequency effects in wave propagation, neglected here, will ultimately have to be taken into account (Dahlen et al 2000;Zhou et al 2006;Fry et al 2008;Peter et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Practically the coda of earthquake records and ambient seismic noise can be used as source wavefield for SI (Campillo 2006;Larose et al 2006) as was first demonstrated by Campillo & Paul (2003) and Shapiro et al (2005). By extracting surface waves (Brenguier et al 2007;Lin et al 2009;Stehly et al 2009) or body waves (Roux 2005;Tonegawa et al 2009;Zhan et al 2010;Poli et al 2012;Lin et al 2013;Nishida 2013) local, regional and global tomographic investigations of the subsurface velocity are among the most widely used applications of SI.…”
Section: Introductionmentioning
confidence: 99%